Novel biomarkers in patients with uncontrolled hypertension with and without kidney damage - Karl Marius Brobak; Lene V. Halvorsen; Hans Christian D. Aass; Camilla L. Søraas; Arleen Aune; Eirik Olsen; Ola Undrum Bergland; Stine Rognstad; Kjersti B. Blom; Jon Arne K. Birkeland; Aud Høieggen; Anne Cecilie K. Larstorp; et al. (Blood Pressure)
Introduction Estimated glomerular filtration rate (eGFR) and urine albumin/creatinine ratio (ACR) are insensitive biomarkers for early detection of hypertension-mediated organ damage (HMOD). In this nationwide cross-sectional study, we assessed potential biomarkers for early HMOD in healthy persons and patients with hypertension. We hypothesised that plasma levels of biomarkers: (1) are different between healthy controls and patients with hypertension, (2): can classify patients with hypertension according to the degree of hypertension severity.Design and methods Patients with hypertension prescribed ≥2 antihypertensive agents were selected from a multicentre study. Healthy controls were selected from an ongoing study of living kidney donor candidates. Uncontrolled hypertension was defined as systolic daytime ambulatory blood pressure ≥135 mmHg. Kidney HMOD was defined by ACR > 3.0 mg/mmol or eGFR < 60 mL/min/1.73 m2. Patients with hypertension were categorised into three groups: (1) controlled hypertension; (2) uncontrolled hypertension without kidney HMOD; (3) uncontrolled hypertension with kidney HMOD. Fifteen biomarkers were analysed using a Luminex bead-based immunoassay, and nine fell within the specified analytical range.Results Plasma levels of Interleukin 1 receptor antagonist (IL-1RA), neutrophil gelatinase-associated lipocalin (NGAL) and uromodulin were significantly different between healthy controls (n = 39) and patients with hypertension (n = 176). In regression models, with controlled hypertension (n = 55) as the reference category, none of the biomarkers were associated with uncontrolled hypertension without (n = 59) and with (n = 62) kidney HMOD. In models adjusted for cardiovascular risk factors and eGFR, osteopontin (OPN) was associated with uncontrolled hypertension without kidney HMOD (odds ratio (OR) 1.77 (1.05–2.98), p = 0.03), and regulated upon activation normal T-cell expressed and secreted (RANTES) with uncontrolled hypertension with kidney HMOD (OR 0.57 (0.34–0.95), p = 0.03).Conclusions None of the biomarkers could differentiate our hypertension groups when established risk factors were considered. Plasma OPN may identify patients with uncontrolled hypertension at risk for kidney HMOD.